2022
DOI: 10.1002/smll.202106592
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Mott−Schottky Ni/CeO2 Heterojunctions into N‐Doped Carbon Nanofibers for High‐Efficiency Electrochemical Water Splitting

Abstract: Designing affordable and efficient bifunctional electrocatalysts for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) has remained a long‐lasting target for the progressing hydrogen economy. Utilization of metal/semiconductor interface effect has been lately established as a viable implementation to realize the favorable electrocatalytic performance due to the built‐in electric field. Herein, a typical Mott–Schottky electrocatalyst by immobilizing Ni/CeO2 hetero‐nanoparticles onto N‐do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 51 publications
7
65
0
Order By: Relevance
“…Similar to what was mentioned previously, the HRTEM image and corresponding Fast Fourier transform pattern (FFT) in Figure 3f,h indicate the {112} planes where the lattice spacing is 3.5 Å and the {200} planes where the lattice spacing is 4.4 Å for CoMoO 4 observed along the [021] axis, as can be indexed from the combination of Figure 3g and its simulated corresponding FFT (Figure 3i). Previous reports have demonstrated that the electronic structure of an active site is highly related to the catalytic activity and could be adequately modulated by constructing heterostructures [30,31]. Hence, X-ray photoelectron spectroscopy (XPS) was employed to study detailed atomic and electronic structural information.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to what was mentioned previously, the HRTEM image and corresponding Fast Fourier transform pattern (FFT) in Figure 3f,h indicate the {112} planes where the lattice spacing is 3.5 Å and the {200} planes where the lattice spacing is 4.4 Å for CoMoO 4 observed along the [021] axis, as can be indexed from the combination of Figure 3g and its simulated corresponding FFT (Figure 3i). Previous reports have demonstrated that the electronic structure of an active site is highly related to the catalytic activity and could be adequately modulated by constructing heterostructures [30,31]. Hence, X-ray photoelectron spectroscopy (XPS) was employed to study detailed atomic and electronic structural information.…”
Section: Resultsmentioning
confidence: 99%
“…3e shows the XPS spectrum of C 1s with three diffraction peaks at 288.8 eV, 286.4 eV, and 284.6 eV belonging to C]O, C-N, and C-C, respectively. 41 In Fig. 3f, the XPS spectrum of N 1s proves the presence of pyrrole N at 400.4 eV and pyridine N at 399.5 eV.…”
Section: Resultsmentioning
confidence: 88%
“…S8, † FeNi 2 S 4 @NiFe-LDH exhibits the highest peak intensity at≈g = 2.003, indicating the highest concentration of oxygen vacancies in FeNi 2 S 4 @NiFe-LDH. 47 These defect sites (oxygen vacancies) could lower the barrier for OH − anion adsorption, which is advantageous for increasing OER activity. 48 The OER electrocatalytic performances of the synthesized catalysts were analyzed using a three-electrode system in 1 M KOH.…”
Section: Resultsmentioning
confidence: 99%